2003
DOI: 10.1016/s0020-7292(03)00333-3
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord prolapse and perinatal outcomes

Abstract: Prolapse of the umbilical cord is an independent risk factor for perinatal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 13 publications
6
53
1
6
Order By: Relevance
“…Prematurity was a cause in 9 (16.98%) patients. Other studies on risk factors associated with cord prolapse have also reported the same factors [7,8] The perinatal mortility in our study was 0.52 per 1000 births. All these deaths were unavoidable as all had absent cord pulsations at the time of presentation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Prematurity was a cause in 9 (16.98%) patients. Other studies on risk factors associated with cord prolapse have also reported the same factors [7,8] The perinatal mortility in our study was 0.52 per 1000 births. All these deaths were unavoidable as all had absent cord pulsations at the time of presentation.…”
Section: Discussionsupporting
confidence: 84%
“…All patients with positive cord pulsations were immediately shifted to operation theatre for urgent LSCS and all had live babies. The fetal maturity in these was 32 weeks (1), 33 weeks -36 weeks (8), rest 32 were >36 weeks. Among these, birth weight of 18 babies was 1.5 kg to 2.5 kg, 23 babies were of 2.6 kg to 3.5 kg, and 2 babies weigh more than 3.6 kg.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study by Kakou C et al, in 92 cases of cord prolapse, they opined that fast care by caesarean could improve significantly the fetal prognosis by relieving the cord compression as early as possible [15] . In a population based study by Kahana et al, they concluded that prolapse of the umbilical cord is an independent risk factor for perinatal mortality [16] . When instrumental delivery is considered, of the various complications of forceps delivery, Intracranial hemorrhage sometimes leading to death can occur.…”
Section: Discussionmentioning
confidence: 99%
“…La procidence du cordon pendant le travail est un accident redouté par les obstétriciens en raison d'un mauvais pronostic foetal [1,2]. C'est un accident rare dont l'incidence est estimée entre 1,5 et deux procidences pour 1000 naissances [3][4][5].…”
Section: Introductionunclassified